Relationships of †Codoichthys carnavalii Santos, 1994 (Teleostei, Clupeomorpha, †Ellimmichthyiformes) from the Late Aptian of São Luís-Grajaú Basin, NE Brazil - FIGUEIREDO,FRANCISCO J. DE (2016)
ABSTRACT †Codoichthys carnavalii is a clupeomorph fish only found in calcareous concretions of Codó Formation, State of Maranhão. It is known based on three specimens housed in the paleontological collection of the Museu de Ciências da Terra of Departamento Nacional da Produção Mineral, Rio de Janeiro. It was omitted in most of recent cladistic analyses about clupeomorphs. We revisited its anatomy furnishing new data and additional restorations. Furthermore we explored the relationships of †Codoichthys with the computer program TNT based on a matrix with 30 taxa and 60 unordered and unweight characters. Elops was used to root the tree. The strict consensus was obtained from three shortest trees (L=181; CI=0.387; RI=0.632). The monophyly of †Ellimmichthyiformes is supported by a sigmoid cleithrum and an uniquely derived predorsal scute series. Most of subgroups showed low support indices. †Sorbinichthyidae and †Horseshoeichthys appear in the most basal position, and not closely related to †Armigatus or †Diplomystus. A †Diplomystus clade is more advanced than †Armigatus and sister-group of remaining †ellimmichthyiforms. Within †Paraclupeidae, †Codoichthys is sister-group of remaining †paraclupeids (including †thorectichthyines and †paraclupeines). Within †Paraclupeinae, †Triplomystini includes a †Triplomystus clade, a sister group of †Rhombichthys plus †Tycheroichthys, and †Paraclupeini with †S. itapagipensis and all other †ellimmichthyiform taxa.